Work satisfaction in a rapidly feminized profession: assessing the intersection of gender, parenting and support resources among veterinary doctors. Issue 2 (3rd March 2020) - Buchanan, Tom; Wallace, Jean E.
Abstract: Women typically hold jobs in which they experience less pay and less favorable working conditions than men in comparable positions. Despite these differences, women report similar or even higher levels of work satisfaction. Most studies explaining work satisfaction and gender focus on workplace rewards as potential explanatory variables. Little is known about the relevance of support resources from the family domain in relation to women's and men's work satisfaction. Finally, the relevance of support resources has not been studied in high-status professions where women have quickly become more highly represented numerically. Using quantitative survey data from a sample of married veterinary doctors ( N  = 311), we explore the influence of work and family-based support resources. Specifically, we examine the relationship between work satisfaction and three sources of support: coworkers, family, and spouses. We also explore whether parental status has moderating effects for women and men with these resources in association with work satisfaction. We find that mothers are more satisfied than fathers. Parenthood and supportive family engagement are strong predictors of women's work satisfaction. Coworker support is a salient predictor of work satisfaction for all, especially for men who are fathers. Implications for men and women working in high-status professions are discussed.